Performance by artists - Bronson, A.A.; Gale, P. (Toronto : Art Metropole, 1979)
Abramovic, Marina & Ulay ; Acconci, Vito ; Anderson, Laurie ; Beuys, Joseph ; Buren, Daniel ; Coum Transmissions ; d'Armagnac, Ben ; Falk, Gathie ; General Idea ; Ontani, Luigi ; Palestine, Charlemagne ; Reindeer Werk ; Robertson, Clive ; Rosenbach, Ulrike ; Sherman, Tom
boek